Validation of the Malay version of pregnancy physical activity questionaire (PPAQ) and the assessment of physical activity, dietary intake and gestational weight gain rate among pregnant women in Kota Bharu, Kelantan - Mamat@Mohamad, Puteri Sulwani (2016)
Gestational weight gain (GWG) plays a vital role in determining pregnancy outcomes. Excessive GWG is the greatest public health concerns as it is related to postpartum weight retention and higher body mass index later in life. Therefore, the present study aimed at assessing validity of Malay Pregnancy Physical Activity Questionnaire (PPAQ-M), dietary intake and physical activity (PA) and also determined GWG predictor factors among pregnant women. Single 24-hour dietary recall was used to assess dietary intake whereas pedometer and validated PPAQ-M were used to assess PA among subjects. The study consisted of two phases, phase I was a validation of PPAQ-M which involved 60 pregnant women wherein phase II was the determination of dietary intake, PA and GWG predictor factors which involved 210 pregnant women who visited selected health clinics for an antenatal check-up in Kota Bharu. Intraclass correlation coefficient (ICC) analysis was used to assess PPAQ-M reliability. Pearson correlation coefficient between total activity value derived from PPAQ-M with step counts obtained from pedometer was used to determine the PPAQ-M validity. Multiple logistic regression was used to determine the GWG predictor factors. ICC value was 0.679 (95% CI 0.515, 0.795) for total activity and ranged from 0.542 to 0.679 for activity intensity including sedentary, light, moderate and vigorous activity. As for type of activity, the ICC value ranged from 0.236 to 0.776 which involved household and caregiving, occupational, sportsor exercise, transportation activity and inactivity. Pearson correlation coefficient showed there was significantly moderate and positive correlation between the total activity with step counts (r = 0.394, p = 0.002). There was a high proportion of inadequate (34.8%) and excessive (44.8%) GWG among subjects. Adjusted multiple logistic regression showed only household income level was a significant predictor of excessive GWG. The current study showed the PPAQ-M had a reasonable reliability and validity which could be used to assess physical activity among pregnant women. The findings on GWG predictor factors suggested pregnant women who were at risk of excessive GWG could be identified early in pregnancy and should be targeted for weight-management interventions during pregnancy or postpartum delivery.